nature and pattern of utilization of seafarers' remittances - Germo, Sarah Mae G.
The Philippines is the second largest migrant sending country and the third largest remittance receiving country in the world. Among the significant contributors of these remittances to the country are the seafarers. The popularization of seafaring led to the increase in the number of Filipino households as recipients of these remittances. The utilization of these remittances by the seafarers? families can affect both households and the country?s economy. The study was undertaken to determine the nature and pattern of utilization of seafarer?s remittances by their families. It generally aims to know nature and pattern of utilization of seafarer?s remittances by their families by (1) determining the profile of the seafarers families, (2) to describe the channels used and schedule of remittances sent by seafarers to their families; (3) to determine the main motivations for sending remitt5ances as perceived by the recipient(s) and; (4) to understand how remittances are utilized by the seafarers? families. The researchers used snowball samp0ling in order to identify the respondents. The data was gathered using the interview schedule and analyzed using simple frequency counts and percentages. The study found that majority of the respondents are spouses of seafarers. Most of the seafarers have two children and majority of them are in grade school. Majority of the seafarers? household are extended type, with at least one relative staying with the family. The result also shows that all of the respondents receive their monthly allotment through the formal method, specifically through banks. The study also recognized that the main motivation of the seafarers for sending remittance to their family is altruism, their unselfish concern for the welfare of their families. Moreover, the study revealed that the primary purpose of the remittance is for personal circumstances, with food as the highest expenditure item. As for the recommendation, the researchers suggested that further studies with a larger sample be made on the nature and patterns of utilization of the seafarers? remittance by their families since the study has limited scope, with only 50 respondents. Furthermore, it is suggested that a parallel study should be conducted in Iloilo City or in more industrialized areas to see the locale?s effect on the nature and pattern of utilization of allotment.